Dental calculus: Nano-characterization - Koruga Đuro; Grga Đurica; Marjanović Marina; Hut Igor; Dželetović Bojan (Serbian Medical Society - Dental Section, Belgrade, 2012)
Emerging technologies and new nanoscale information have potential to transform dental practice by improving all aspects of diagnostics and therapy. Nanocharacterization allows understanding of oral diseases at molecular and cellular levels which eventually can increase the success of prevention and treatment. Opto-magnetic spectroscopy (OMS) is a promising new technique based on light-matter interaction which allows insight into the quantum state of matter. Since biomolecules and tissues are usually paramagnetic or diamagnetic materials it is possible to determine the dynamics of para-and diamagnetism at different teeth structures using that method. The topography of the surface of a sample can be obtained with a very high resolution using atomic force microscopy (AFM), which allows observation of minimal changes up to 10 nm, while magnetic force microscopy (MFM) is used to record the magnetic field gradient and its distribution over the surface of a sample. The aim of this study was to determine the possibility of AFM and MFM for the characterization of dental calculus, and a potential application of OMS for the detection of subgingival dental calculus.